The Influence of Primed Seed with KNO3, KH2PO4 and GA3 on Germination and Seedling Growth of Water Morning Glory (Ipomoea aquatica Forsk. Var. reptan) - Kangsopa, Jakkrapong; Jeephet, Phetcarat; Atnaseo, Chuthamat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2021)
Water morning glory is one of the popular vegetables used in cooking among Thai people, such that there are widely established water morning glory seed business. However, industrial scale production of water morning glory is faced with problems of easily deteriorating seeds resulting in slowed and uneven germination and abnormal seedling. Therefore, the objective of this experiment was to find suitable ratio of KNO3, KH2PO4 and GA3 for the priming of morning glory seeds and to observe changing in germination rate, seedling vigor and growth parameter of morning glory seedlings. Study was conducted at the seed technology laboratory, Faculty of Agricultural Production, Maejo University. Eleven different treatments were separately applied to morning glory seeds, which included no treatment, and treating by priming with distilled water, with 1, 2 or 3 % of KNO3 (% W/V), with 1, 2 or 3 % of KH2PO4, and with 0.02, 0.05 or 1 % of GA3 (% W/V). It was found that water morning glory seeds primed with 2 % KH2PO4 displayed the increases in radicle emergence, speed of radicle emergence, germination percentage, speed of germination and germination index when compared to untreated seeds. Priming with 1 % GA3 resulted in higher germination rate of primed seeds compared to unprimed seeds. Moreover, priming with 1 % GA3 also resulted in increasing seedling shoot length and total seedling length that were different, statistically, when compared primed to unprimed seeds.